PERSEPSI MASYARKAT TERKAIT VAKSINASI VIRUS COVID-19 DI KOTA PERAWANG KECAMATAN TUALANG KABUPATEN SIAK - Pioni Auzella Wahyuni; Ringgo Eldapi Yozani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Corona Virus Disease 2019 or commonly abbreviated as COVID-19 is an infectious disease caused by SARS-CoV-2, a type of corona virus. People with COVID-19 may experience fever, dry cough, and difficulty breathing.With this COVID-19 vaccine, of course, this is good news for people in all parts of the world, especially in the Perawang community, Tualang District, Siak Regency. However, not all people directly accept and want to be vaccinated, not a few people are still doubtful about the vaccine and tend to reject it because there are still many of them who do not understand well about this COVID-19 vaccine.This study uses descriptive qualitative research methods with purposive techniques where the informants consist of 8 people from Perawang community, Tualang District, Siak Regency, including 2 people with high education, 4 general public, and 2 community leaders. Collecting data using unstructured interview techniques, non-participant observation and documentation. The data analysis technique used the Miles and Hubermann interactive data model by validating the data using the participation extension and triangulation techniques.Keywords: Perception-vaccine-Covid19-Siak